Perancangan Strategi Digital Marketing untuk Meningkatkan Promosi UMKM Ubay Singkong Keju - Alfin Hakim Abdillah; Irdha Yunianto (Pusat Riset dan Inovasi Nasional, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economy by creating jobs, reducing poverty, and contributing to the Gross Domestic Product (GDP). However, many MSMEs still struggle to market their products effectively. Limited capital, workforce, and access to promotional media lead them to rely on conventional methods such as print advertising, with minimal use of digital platforms. These limitations hinder their ability to reach wider markets and compete effectively at both local and national levels. Furthermore, differences in approach between MSMEs and large companies influence their marketing strategies. MSMEs often prioritize social networks and personal relationships over structured and systematic marketing plans. As a result, traditional methods are insufficient to face increasing competition and shifts in consumer behavior. Therefore, research was conducted on more innovative, creative, and adaptive marketing strategies for Ubay Singkong Keju MSMEs so that they could survive and thrive amid the ever-changing market dynamics.